DETERMINANT FACTORS OF AIR QUALITY: EMPIRICAL STUDY IN JAVA ISLAND - Havidz Aldi Setiawan; Muhammad Lutfi; Dwi Rahmayani (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
Air pollution is one of several environmental problems faced by several countries in the world, including Indonesia. Air pollution caused many environmental problems such as global warming and climate change. Air pollution increased due to human activity and economic development. Economic activities such as industry, infrastructure development to community mobility can affect air quality in an area. The study aimed to analyze the impact of income per capita, transportation, and population on the air quality of six provinces in Java Island. This study obtained data from the National Statistic Central Bureau and the Ministry of Forestry websites from the year 2013-to 2019. This study was using a quantitative method through the regression model with panel data to achieve the research's goals. The result showed that the variable of income per capita has negative effects on air quality. The variable of income per capita is described by the economic activity of people in Java Island. The results of this study indicate that the economic activities of people in Java Island still have a negative impact on the environment, especially on the air quality. The opposite result was obtained from transportation and population variables that have a positive effect on air quality in the six provinces in Java Island from 2013 to 2019.